The Effect of Problem-Based Learning and Learning Motivation on Descriptive Writing Skills - Farhan Elbi Rosyid; Syahrul R; Yeni Karneli; Muhammadi Muhammadi (FKIP - Universitas Riau, 2026)
This study was conducted to address the low descriptive writing skills of elementary school students, which are commonly indicated by limited vocabulary, weak idea organization, and insufficient detail. The purpose of this study was to examine the effect of the Problem-Based Learning (PBL) model and learning motivation on the descriptive writing skills of fourth-grade students. This research employed a quantitative approach using a quasi-experimental method with a 2 × 2 factorial design. The participants consisted of two fourth-grade classes, with one class taught using the PBL model and the other using conventional instruction. Data were collected through a descriptive writing performance test and a learning motivation questionnaire that met validity and reliability requirements. The data were analyzed using descriptive statistics and a two-way ANOVA. The results showed that the PBL model had a significant effect on students’ descriptive writing skills, and learning motivation also had a significant effect. However, no significant interaction was found between the learning model and learning motivation. In conclusion, the PBL model is effective in improving descriptive writing skills regardless of students’ learning motivation levels.